Metapsychology of sadism-masochism in Freud and its relation to the drive theories: double affectation in Freudian theory - Dutra da Cunha, Renan; Omar Perez, Daniel (Sofia, 2026)
This work proposes an analysis of the concepts of sadism and masochism in Freud’s works, with the aim of showing how the theory of sadism-masochism and the drive theories were articulated and mutually influenced each other. In his first drive theory, Freud associates sadism with the aggressive component of the drive that became exacerbated and independent, consequently dominating the subject’s sexual tendency, while masochism is considered a continuation of sadism turned back against the person themselves. In the second drive theory, with the introduction of the death drive, the emphasis previously placed on sadism moves to masochism, now considered as primary. Masochism would correspond to the part of the death drive that remained bound to the libido and retained within the organism, and sadism, the portion of that drive deflected toward external objects and placed in the service of the sexual function. We conclude that not only did the introduction of the concept of death drive into Freud’s work imply an important reformulation in his theory of sadomasochism, but the concepts of sadism and masochism themselves also exerted, in a certain way, an influence on the reformulation of his theory of drives.